REVIEW OF MEDICINAL USES, PHYTOCHEMISTRY, AND PHARMACOLOGICAL PROPERTIES OF DRIMIA ELATA - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Drimia elata is an important and well-known medicinal plant in tropical Africa. This study critically reviewed the medicinal applications, phytochemistry, and pharmacological activities of D. elata. Literature on medicinal applications, phytochemical, and pharmacological activities of D. elata was collected from multiple internet sources including Elsevier, Google Scholar, SciFinder, Web of Science, PubMed, BMC, ScienceDirect, and Scopus. Complementary information was gathered from pre-electronic sources such as books, book chapters, theses, scientific reports, and journal articles obtained from the university library. This study showed that D. elata is used for treating several medical conditions, particularly general ailments, blood and cardiovascular system, reproductive system and sexual health, urinary system, infections and infestations, digestive system, respiratory system, and muscular-skeletal system disorders. Phytochemical compounds identified from the species include bufadienolides, alkaloids, aromatic acids, flavonoids, phlobatannins, saponins, steroids, tannins, and terpenoids. Ethnopharmacological research revealed that D. elata extracts have acetylcholinesterase enzyme inhibitory, antibacterial, antifungal, antimycobaceterial, anticancer, anti-inflammatory, antioxidant, hemagglutinating, and cytotoxicity activities. D. elata should be subjected to extensive in vivo experiments and also future studies should focus on how potential toxic components of the species can be managed when it is used as herbal medicine.